2011
DOI: 10.1259/bjr/50130643
|View full text |Cite
|
Sign up to set email alerts
|

The detection and discrimination of malignant and benign focal hepatic lesions:T2weightedvsdiffusion-weighted MRI

Abstract: Objective: The purpose of this study was to evaluate the use of diffusion-weighted imaging (DWI) for the detection and characterisation of focal hepatic lesions compared with the use of T 2 weighted imaging. Method: 45 patients with 97 hepatic lesions (51 malignant lesions and 46 benign lesions) were included in this retrospective study. Malignant hepatic lesions included 12 hepatocellular carcinomas, 26 metastases and 13 intrahepatic cholangiocarcinomas. Benign hepatic lesions included 19 haemangiomas and 27 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
3
21
0
Order By: Relevance
“…DWI has a higher detection rate of liver tumors than T2WI[64,65], particularly in detecting malignant lesions[66]. However, the ADC of benign solid lesions has been reported to be similar to that of the liver parenchyma[67].…”
Section: Detection and Characterization Of Liver Tumorsmentioning
confidence: 99%
“…DWI has a higher detection rate of liver tumors than T2WI[64,65], particularly in detecting malignant lesions[66]. However, the ADC of benign solid lesions has been reported to be similar to that of the liver parenchyma[67].…”
Section: Detection and Characterization Of Liver Tumorsmentioning
confidence: 99%
“…The extracted useable data and the study characteristics of each article are summarized in Table 1. In the study by Yang et al, [32] an analysis of DWI images was performed independently by 2 observers; thus, 2 subsets of data from the study were included. Therefore, we extracted 9 subsets of data from all 8 studies.…”
Section: Resultsmentioning
confidence: 99%
“…[2426] With the current development of the advanced respiratory gating technique and sensitivity encoding, abdominal DW-MRI has been increasingly used in diseases of the liver, the imaging of which was formerly restricted by respiratory movement. DWI has been used to assess the degree of hepatic fibrosis, [2730] detect hepatic lesions, [3134] and differentiate malignant from benign lesions [32,3541] independently from T1 and T2 relaxation times and without the need for contrast agent administration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique may be useful in determining pathology in the liver (degree of cirrhosis/fibrosis), kidneys (lesion characterization, renal failure, pyelonephritis), pancreas (pancreatitis and pancreatic cancer), bowel (Crohn's disease), and uterus (endometriosis) [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] . In a recent meta-analysis, Li et al [19] has shown a potential future role for this type of sequence to assess for cancers within the liver.…”
Section: Introductionmentioning
confidence: 99%